Determinants of Profitability in Indonesian Islamic Banks: A Study on Financing to Deposit Ratio - Wahyudi, Tri; Sari Pohan, Erlina (Perbanas Journal of Islamic Economics and Business, 2024)
This study investigates the impact of the Financing to Deposit Ratio on the profitability of Islamic commercial banks in Indonesia, with a specific focus on Return on Assets as the profitability metric. Despite the significant growth of Islamic banking in Indonesia, the challenge of maintaining profitability remains critical. This study uses a population of all Islamic commercial banks operating in Indonesia from 2015 to 2019, with eightbanks selected through a purposive sampling method. The analysis involved classical assumption tests including normality, multicollinearity, autocorrelation, and heteroskedasticity tests, followed by regression analysis. The results indicate that Financing to Deposit Ratio does not have a statistically significant effect on Return on Assets. These findings challenge the assumption that Financing to Deposit Ratio is a primary determinant of profitability in Islamic banks and suggest that other factors and financial indicators must be considered. The study underscores the importance of comprehensive financial management strategies and robust risk management practices. It also highlights the relevance of agency and signaling theories in improving governance and financial performance. The findings provide valuable insights for bank managers and policymakers to enhance the financial health and sustainability of Islamic commercial banks in Indonesia. Further research should explore additional variables and more complex models to deepen the understanding of profitability determinants in Islamic banking.